Aquatic genetic resources: Policies and regulatory mechanisms including lessons learnt from indigenous and ancient knowledge - KUMAR, DILIP; SHARMA, RUPAM; DESHMUKHE, GEETANJALI (The Indian Journal of Animal Sciences, 2010)
India possesses rich biodiversity of both terrestrial and aquatic flora and fauna along with ancient and traditional knowledge for its utilization as food, medicine, etc. The traditional knowledge along with its methods for conservation strategies is needed to be documented and brought forward to draw suitable policies and formulate regulatory mechanism to conserve the aquatic bioresources and to reproduce them in sustainable environment friendly manner. Stakeholders’ participation is the key to achieve such goals since the local communities and tribes possess the key knowledge of the region’s bioresources and environmental phenomenon.